Darbepoetin Alfa in Young Infants With Renal Failure: Single Center Experience, a Case Series and Review of the Literature - Libudzic-Nowak, Anna Maria; Cachat, Francois; Pascual, Manuel; Chehade, Hassib (Frontiers in Pediatrics, 2018)
Background: Anemia treatment in infants with advanced or chronic kidney disease (CKD) represents an important challenge. The use of darbepoetin alfa, a novel erythropoiesis stimulating agent, has largely replaced recombinant human erythropoietin in older children and in adults with CKD. However, studies reporting the use of darbepoetin alfa in infants below 1 year of age are sparse. Case presentation: We report the data of three infants with advanced stage kidney failure, aged 1, 4 and 7 months, who were treated with darbepoetin alfa and followed for 18 to 41 months. Hemoglobin levels increased in all 3 patients, reaching the target levels of 10.7-12 g/dl by 11, 19 and 22 weeks respectively, without any documented adverse effects. Patients younger than 1 year of age required a larger darbepoetin alfa dosage (ranged from 1.2 to 2.9 μg/kg per month) as compared to older children. A review of the literature found only 3 studies using darbepoetin alfa successfully in such young infants. Conclusion: In these 3 patients with advanced kidney disease, darbepoetin alfa was effective in correcting anemia with no observed adverse effects.